2001
DOI: 10.1063/1.1386640
|View full text |Cite
|
Sign up to set email alerts
|

Zonal flow and field generation by finite beta drift waves and kinetic drift-Alfvén waves

Abstract: A study of the generation of zonal flows and zonal magnetic fields by finite beta drift waves and kinetic drift-Alfvén waves is presented. The analysis is a generalization of recent investigations of the modulational instability for zonal flow generation by electrostatic drift waves to finite beta drift waves and kinetic drift-Alfvén waves. The drift wave driven unstable zonal flows/fields are stabilized by finite β below a critical value, due to the finite beta modification of the drift wave pump and the drif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…This representation is the local version of the decomposition used by Chen et al, 19 and the complex representation of that used by Guzdar. 20,21 Inserting Eq. ͑8͒ into Eqs.…”
Section: Theoretical Modelmentioning
confidence: 98%
“…This representation is the local version of the decomposition used by Chen et al, 19 and the complex representation of that used by Guzdar. 20,21 Inserting Eq. ͑8͒ into Eqs.…”
Section: Theoretical Modelmentioning
confidence: 98%
“…Motivated by the experimental discovery of a low-to-high (LH) transition in the plasma confinement, experimental and theoretical works in the two last decades have focused on whether the turbulence associated with the H-mode might be regulated by interactions with ZFs or shear flows. In particular the generation of zonal flow by finite beta drift waves or kinetic drift wave was investigated by Guzdar et al in [5,6] showing the importance of parametric-type processes in the LH transition.…”
Section: Introductionmentioning
confidence: 99%
“…The coherent mode coupling model used in this particular study has been adopted and fitted to this field of study in recent years [6][7][8][9][10][11][12][13][14]. It has been shown that the model is in good agreement with the corresponding model derived using the wave kinetic equation [13] and the model has successfully contributed to better understanding of the weak generation of zonal flows in recent measurements at the Columbia Linear Machine [14].…”
Section: Introductionmentioning
confidence: 85%